Contemporary Carioca Technologies of Mixing in a Brazilian Music Scene - Moehn, Frederick (Duke University Press, 2012)
Brazilian popular music is widely celebrated for its inventive amalgams of styles and sounds. Cariocas, native residents of Rio de Janeiro, think of their city as particularly conducive to musical mixture. Contemporary Carioca introduces a generation of Rio-based musicians who collaboratively have reinvigorated Brazilian genres, such as samba and maracatu, through juxtaposition with international influences, including rock, techno, and funk. He describes how these artists manage their careers, having reclaimed some control from record labels. Examining the specific meanings that their fusions have in the Carioca scene, he explains that musical mixture is not only intertwined with nationalist discourses of miscegenation, but also with the experience of being middle-class in a country confronting neoliberal models of globalization. Moehn offers vivid depictions of Rio musicians as they creatively combine and reconcile local realities with global trends and exigencies.